Promoting cultural and social values in Yoruba nollywood movies (2017)
Yoruba Nollywood movies have been both applauded for promoting cultural and social values which results in Nigeria’s progress and denounced as a form of projecting Nigeria’s bad image by films critics. Against this backdrop, the study examined audience preference of Yoruba films and how they have promoted their cultural and behavioural values. Employing survey technique, evidence shows that the audience favoured certain Yoruba films, casts and producers. Two, their thematic interests include injustices, extra-marital affair, get-rich syndrome, ritualism, power tussle, armed robbery and bribery and corruption, while integrity/honesty, cultural identity and hard work form the fulcrum of their socio-cultural values. In the end, Yoruba film audience determine what they cultivate from mediated social realities as cultural and social values.